Initiation and termination of cyclic nucleotide action - Corbin, Jackie D.; Johnson, Roger A. (Methods in enzymology ;, 1988)
Novel approaches for the study of phosphodiesterases and phosphoprotein phosphatases, as well as those of nonmammalian cyclic nucleotide receptors, are emphasized for the first time in the Methods of Enzymology series. New methods for the study of protein kinases are also presented.